Significant Correlation between Cystatin C, Cerebral Infarction, and Potential Biomarker for Increased Risk of Stroke - Zeng, Qiong; Lin, Kun; Yao, Mianxuan; Wei, Liling (Current Neurovascular Research, 2015)
This study investigated the correlation of serum cystatin C levels with cerebral infarction (CI) and different subtypes of CI, the severity of CI and the risk of recurrent CI. Totally 1017 patients with CI and 534 healthy controls were included, with clinical and biochemical characteristics documented and analyzed. The results showed serum cystatin C were 0.93 ± 0.21 mg/l and 1.19 ± 0.5 mg/l in control and CI, respectively (p < 0.001). The significant risk factors for CI were age (p < 0.001, OR = 1.048), presence of diabetes (p = 0.007, OR = 2.397), cystatin C (p = 0.001, OR = 1.021), uric acid (p = 0.017, OR = 4.226), and systolic blood pressure (p = 0.021, OR = 1.003). The risk of CI increased with cystatin C levels. Also, cystatin C levels were associated with different subtypes of CI, with large-artery atherosclerosis (LAA) subtype having the highest level of cystatin C. Moreover, cystatin C levels were significantly and positively correlated with Essen Stroke Risk Score (ESRS). The higher level of cystatin C the higher risk of recurrent stroke. In contrast, correlation between cystatin C levels and National Institute of Health stroke scale (NIHSS) score was not significant. In conclusion, cystatin C was an independent risk factor for CI. LAA subtype of CI was more closely related to increased cystatin C level. Furthermore, cystatin C levels predict risk of recurrent CI but not the severity of CI.
Keywords: Essen Stroke Risk Score